Retransmission-Based Additional TXOP Allocation for Audio-Video Transmission by IEEE 802.11e HCCA - Muhamad Noh, Z. A.; Md Khambari, M. N.; Mat Ariff, N. A.; Roslan, I. (2011)
This paper proposed a method of allocating additional TXOP duration to replenish the bandwidth used during the retransmission of frames at link layer in audio-video transmission by IEEE 802.11e HCCA. In the proposed scheme, the HC monitors the number of retransmission at link layer and utilize the surplus bandwidth to allocate additional TXOP duration on the basis of number of retransmission performed during the last transmission. The proposed scheme also reduces the polling overhead to gain surplus bandwidth by polling only a station in a polling interval. By simulation, we compare the application-level QoS of the TGe scheme and the proposed scheme. Numerical results show that the proposed scheme can keep the QoS of audio and video high under lossy wireless channel especially when the number of multimedia stations is small. Furthermore, the proposed scheme can admit more traffic flows than the TGe scheme.